Leishmania chagasi infection in cats with dermatologic lesions from an endemic area of visceral leishmaniosis in Brazil - Vides, Juliana Peloi [UNESP]; Schwardt, Tatianna Frate [UNESP]; Vicente Sobrinho, Ludmila Silva [UNESP]; Marinho, Márcia [UNESP]; Laurenti, Marcia Dalastra; Biondo, Alexander Welker; Leutenegger, Christian; Marcondes, Mary [UNESP] (Elsevier B.V., 2011)
Although dogs are considered the main domestic reservoirs for Visceral Leishmaniosis (VL), which is caused in the Americas by Leishmania chagasi, infected cats have also been recently found in endemic areas of several countries and became a public health concern. Accordingly, the purpose of this study was to evaluate cats with dermatologic lesions from an endemic area of VL and the natural infection of L. chagasi. A total of 55 cats were selected between April 2008 and November 2009 from two major animal shelters of Aracatuba, Southeastern Brazil. All cats underwent general and dermatologic examinations, followed by direct parasitological examination of lymphoid organs, immunosorbent assay (ELISA) and indirect immunofluorescence (IFAT). In addition, detection of amastigotes was performed by immunohistochemistry (IHC) in skin lesions of all cats. VL was diagnosed in 27/55 (49.1%) cats with dermatological problems. Amastigotes were found in lymphoid organs of 10/27 (37.0%) cats; serology of 14/27 (51.9%), 6/27 (22.2%) and 5/27 (18.5%) cats was positive for ELISA, IFAT and both, respectively. The IHC identified 9/27 (33.3%) cats; 5/27 (18.5%) were positive only for IHC and therefore increased the overall sensitivity. Specific FIV antibodies were found in 6/55(10.9%) cats, of which 5/6 (83.3%) had leishmaniosis. Real time PCR followed by amplicon sequencing successfully confirmed L chagasi infection. In conclusion, dermatological lesions in cats from endemic areas was highly associated to visceral leishmaniosis, and therefore skin IHC and differential diagnosis of LV should be always conducted in dermatological patients in such areas. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: Feline leishmaniosis; ELISA; IFAT; Immunohistochemical; RT-PCR